Donor-Specific Antibodies, C4d and Their Relationship With the Prognosis of Transplant Glomerulopathy. Issue 1 (January 2015) - Lesage, Julie; Noël, Réal; Lapointe, Isabelle; Côté, Isabelle; Wagner, Eric; Désy, Olivier; Caumartin, Yves; Agharazii, Mohsen; Batal, Ibrahim; Houde, Isabelle; De Serres, Sacha A.
<x xml:space="preserve">Abstract</x> Background Transplant glomerulopathy (TG) is a diagnostic criterion for chronic active antibody-mediated rejection (CAABMR), with C4d, donor-specific antibodies (DSA) and other lesions of chronic tissue injury. However, TG often presents without C4d or DSA. Until recently, such cases were termed suspicious for CAABMR, and their prognosis remains unclear. Methods To better understand the contribution of TG, C4d, and DSA on outcomes, we retrospectively studied 61 patients with late TG for the composite endpoint of death-censored graft failure or doubling of serum creatinine. Cases were matched to controls based on age, year and number of transplant, type of donor, and the availability of an indication biopsy during the same time after transplantation. Analyses were performed using proportional hazards models. Results Compared to matched controls, patients with TG had a more than fivefold increased risk of reaching the endpoint (adjusted hazard ratio (aHR), 5.3; 95% confidence interval (95% CI), 1.5-18.4). The proportion of patients with isolated TG, TG suspicious for CAABMR (C4+/DSA− or C4d−/DSA+) and TG with definite CAABMR (C4d+/DSA+) were 63%, 20%, and 17%, respectively. Suspicious and definite CAABMR showed a similar prognosis, significantly worse than isolated TG (aHR, 4.5; 95% CI, 1.1-18.9 and aHR, 5.9, 95% CI, 1.1-31.3 respectively). Conclusion Transplant glomerulopathy is associated with poor prognosis, independent of the level of graft dysfunction and other chronic histologic changes. This prognosis is similar whether there is evidence of tissue or peripheral alloantibody reactivity. These findings are relevant to the development of clinically meaningful criteria for CAABMR, for its clinical management, and in the future selection of population for clinical trials.